Stimuli‐Responsive Sponge for Imaging and Measuring Weak Compression Stresses (Adv. Sci. 3/2023). Issue 3 (25th January 2023) - Ono, Nahoko; Seishima, Ryo; Okabayashi, Koji; Imai, Hiroaki; Fujii, Syuji; Oaki, Yuya
Abstract : Stimuli‐Responsive Sponges In article number 2206097, Nahoko Ono, Syuji Fujii, Yuya Oaki, and co‐workers show stress‐imaging sponge device combining stimuli‐responsive conjugated polymer and capsule materials. The sponge device visualizes and quantifies the local compression stress and its distribution applies by irregularly shaped objects. The stress distribution caused by surgical device is visualized to solve a couple of clinical issues.